Avaliação microbiológica da superfície dos implantes ortopédicos metálicos usados para fixar fraturas ósseas - dos Santos, Cássio Antonio Lanfredi [UNESP]; Pizzolitto, Elisabeth Loshchagin [UNESP]; de Campos Júnior, Flávio Ferraz; Bernardi, Adilson César Abreu; Leite, Clarice Queico Fujimura [UNESP] (My University, 2012)
In the majority of cases of bone fracture requiring surgery, orthopedic implants (screw-plate and screw) are used for osteosynthesis and the infections associated with such implants are due to the growth of microorganisms in biofilms. The objective of this study was to identify microorganisms recovered from osteosynthesis implants used to fix bone fractures, to assess the viability of the cells and the ability of staphylococci to adhere to a substrate and to determine their sensitivity/resistance to antimicrobials. After surgical removal, the metal parts of austenitic stainless steel (ASTM F138/F139 or ISO NBR 5832-1/9) were transported to the Laboratory of Clinical Microbiology, washed in buffer and subjected to ultrasonic bath at 40±2 kHz for 5 minutes. The sonicated fluid was used to seed solid culture media and cell viability was assessed under the microscope by with the aid of a fluorescent marker. The production of extracellular polysaccharide by Staphylococcus spp. was investigated by means of adhesion to a polystyrene plate. The profile of susceptibility to antimicrobials was determined by the disk diffusion assay. The most frequently isolated bacteria included coagulase-negative Staphylococcus resistant to erythromycin, clindamycin and oxacillin. Less frequent were Pseudomonas aeruginosa resistant to trimethoprim/sulfamethoxazole and ampicillin, Acinetobacter baumannii resistant to ceftazidime, Enterobacter cloacae resistant to cephalothin, cefoxitin, cefazolin, levofloxacin and ciprofloxacin, Bacillus spp. and Candida tropicalis. The observation of slides by fluorescence microscope showed clusters of living cells embedded in a transparent matrix. The test for adherence of coagulase-negative Staphylococcus to a polystyrene plate showed that these microorganisms produce extracellular polysaccharide. In conclusion, the metal parts were colonized by bacteria related to orthopedic implant infection, which were resistant to multiple antibiotics.

A maioria dos casos de fraturas ósseas é utilizada nas cirurgias, implantes ortopédicos de osteossíntese (placa-parafuso e parafusos) e a infecção associada ao implante está relacionada com crescimento de microrganismos em biofilme. O objetivo deste estudo foi identificar os microrganismos recuperados de implantes de osteossíntese usados para fixação de fratura óssea, avaliar a viabilidade celular, a capacidade de aderência dos estafilococos e, determinar o perfil de sensibilidade/resistência aos antimicrobianos. Após a remoção cirúrgica, os conjuntos metálicos de aço inoxidável austenítico ASTM F138/F139 ou ISO NBR 5832-1/9 foram enviados ao Laboratório de Microbiologia Clínica, lavados em solução tampão e submetidos ao banho ultrassônico em 40±2 kHz por 5 minutos. O fluido sonicado foi semeado em meios de cultura e a viabilidade celular foi avaliada por meio de marcador fluorescente. A produção de polissacarídeo extracelular por Staphylococcus spp. foi averiguada por meio do teste de aderência em placa de poliestireno. O perfil de sensibilidade/resistência foi determinado por meio de técnica do disco difusão. As bactérias mais isoladas incluíram Staphylococcuscoagulase-negativa resistente à eritromicina, oxacilina e clindamicina. Em menor freqüência, Pseudomonas aeruginosa resistente à sulfametoxazol/trimetoprim e ampicilina; Acinetobacter baumanniiresistente à ceftazidima; Enterobacter cloacaeresistente à cefalotina, cefoxitina, cefazolina, levofloxacina, ciprofloxacina; Bacillus spp. e Candida tropicalis. A observação ao microscópio de fluorescência demonstrou agrupamentos celulares vivos envoltos em substância transparente. O teste de aderência dos Staphylococcuscoagulase-negativa à placa de poliestireno mostrou que estes microrganismos são produtores de polissacarídeo extracelular. Em conclusão, os conjuntos metálicos foram colonizados por bactérias relacionadas à infecção de implantes ortopédicos, os quais apresentaram resistência múltipla aos antimicrobianos.
Microbiological analysis of the surface of metal orthopedic implants used to fix bone fractures
Keywords: Austenitic stainless steel; Bacterial resistance; Biofilm; Orthopedic implants; Osteosynthesis; Sonication; ampicillin; cefalotin; cefazolin; cefoxitin; ceftazidime; ciprofloxacin; clindamycin; cotrimoxazole; erythromycin; levofloxacin; oxacillin; polysaccharide; Acinetobacter baumannii; antibiotic resistance; antibiotic sensitivity; Bacillus; bacterial colonization; bacterium adherence; bacterium isolation; Candida tropicalis; cell viability; coagulase negative Staphylococcus; disk diffusion; Enterobacter cloacae; fluorescence microscopy; fracture; microbiological examination; microscopy; nonhuman; orthopedic implant; Pseudomonas aeruginosa